Low-intensity extracorporeal shock wave therapy for patients with severe erectile dysfunction due to radical prostatectomy - Inoue, Shogo; Kurimura, Yoshimasa; Sadahide, Kosuke; Hayashi, Tetsutaro; Teishima, Jun; Higashi, Yukihito; Matsubara, Akio (Annals of Research Hospitals, 2017)
Background: Phosphodiesterase type 5 inhibitor (PDE5I) was proved to be effective for normal treatment, but the response rate of PDE5I is significantly low in patients with erectile dysfunction (ED) due to radical prostatectomy (RP). Low-intensity extracorporeal shockwave therapy (LI-ESWT) was proved to be useful as a safe modality to treat ED. My objective is to determine the efficacy of LI-ESWT for patients with severe ED due to RP. Methods: This study was an open-label prospective pilot study. Between September 2012 and May 2014, 12 patients with severe ED due to RP were enrolled into this protocol. LI-ESWT comprised two treatment sessions per week for three weeks, which were repeated after a three-week no-treatment interval. LI-ESWT was applied to the penile shaft and crura at five different sites. Assessment of erectile and sexual function during LI-ESWT was determined using the international index of erectile function-erectile function domain (IIEF-EF) score, erection hardness score (EHS), nocturnal penile tumescence (NPT), flow-mediated vasodilation (FMD), and adverse events. We used FMD with the plethysmography technique for objective evaluation of the participant’s penile hemodynamics and endothelial function (EnF). Results: At the one-month follow up examination, the IIEF-EF scores did not change after LI-ESWT. However, the erectile function parameters significantly improved from 0.50±0.19 to 1.13±0.30 for EHS (P=0.0078) and from 0.36±0.14 to 1.06±0.36 for NPT (P=0.0156). Also, the FMD parameters significantly improved from 13.8±1.3 to 24.0±2.5 (P=0.0032). None of the patients reported adverse events. Conclusions: This is the first study that assessed the efficacy of LI-ESWT for patients with severe ED due to RP. Based on our results, LI-ESWT appeared to have the potential to be an effective treatment option for severe ED patients.